Pelestarian Arsitektur Pascabencana Tsunami sebagai Cagar Budaya (Studi Kasus : Masjid Baiturrahim, Banda Aceh, Indonesia) - Zya Dyena Meutia; Zardan Araby (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2023)
Abstract. The Baiturrahim Ulee Lheue Mosque has significant value as a cultural cagar budaya that has experienced various layers of excellence at any time in the Banda Aceh. The building that has been more than 500 years old has become one of the oldest mosques in Indonesia with an incredible history. The Baiturrahim mosque was the only building to survive from the 2004 Tsunami natural disaster. The architecture of the mosque is rich in value, meaning and symbols,which are also evidence of the history of civilization and the aearly development of Islam in Aceh. Currentyly, there is a decline in the physical quality and meaning of the architectural elements of the building, especially the architectural elements after the tsunami disaster. This affects the historical value and cultural meaning of the building. This study aims to know preservation strategy based on significance values of the Baiturrahim Ulee Lheue Mosque as a cultural heritage. The method used in this research is descriptive-qualitative through filed observation, documentation/ an interview and literature review. The approach of handling refers to some references and guidelines for the preservation of a cultural heritage building that has significant values like history, age, spiritual and aesthetic. Preservation efforts are required development use and protection of the architectural mosque of Baiturrahim as heritage building.